2020
DOI: 10.4236/jtts.2020.102008
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study for Feasibility of Driver Agent in Actual Car Environment<br/>—Driver Agent for Encouraging Safe Driving Behavior (3)

Abstract: Japan has become a more aged society and there are more drivers, 65 years of age and above. Cars represent an important mode of transportation for the elderly; however, in recent years, the number of traffic accidents caused by elderly drivers has been on the rise, and this has become a social issue. Thus, for the elderly drivers to encourage them to improve their driving, we study a driver agent system which consists of smartphone, communication robot and cloud service and provides the driving support by atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 8 publications
0
12
1
Order By: Relevance
“…A driving support agent (DSA) is used as an engineering support method for manual driving (Figure 1). Previous studies on DSA [1][2][3] have shown the effectiveness of small dashboard robots, which assist the driver through voice utterances. In addition, research on DSA is a hot topic in the human-agent interaction (HAI) community, and a study of DSA [3] won the Best Paper Award at the International Conference on HAI 2017.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…A driving support agent (DSA) is used as an engineering support method for manual driving (Figure 1). Previous studies on DSA [1][2][3] have shown the effectiveness of small dashboard robots, which assist the driver through voice utterances. In addition, research on DSA is a hot topic in the human-agent interaction (HAI) community, and a study of DSA [3] won the Best Paper Award at the International Conference on HAI 2017.…”
Section: Introductionmentioning
confidence: 99%
“…The main utterances of previous DSAs [1][2][3] were designed to give implicit instructions to avoid causing discomfort to the user (e.g., the DSA says "there is a pedestrian" and does not specify the driving behaviors the user should perform). According to politeness theory [4], a knowledge in the research field of sociolinguistics and pragmatics, such implicit instruction corresponds to the "hinting" strategy (off-record), which avoids directly communicating intentions to the other party.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations